Reconstruction of special sentencing guidelines on state loss crime in the Indonesian Criminal Code - Andi Muhammad Alief (Integritas: Jurnal Antikorupsi, 2024)
State loss crimes are regulated by two laws: Act 31/1999 and Act 1/2023 (KUHP). The regulation of state loss crimes in the KUHP replaces the regulation of state loss crimes in Act 31/1999. Three years after January 2, 2023, Perma 1/2020 will not apply, so there are no special sentencing guidelines to apply the state loss crime article of KUHP. Such sentencing guidelines are required to minimize unwarranted disparities. This study aims to prevent a legal vacuum and unwarranted disparity from occurring when the KUHP comes into effect. The methods of this research include the normative legal type, statutory approaches, conceptual approaches, primary and secondary data sources and qualitative analysis. Sentencing guidelines for state-loss crimes present several problems. First, Perma 1/2020 does not follow the regulations for the formation of legislation, the material on the criminal sanctions range is contrary to the principle of legality and is weak from a juridical aspect. Second, the sentencing guidelines in the KUHP do not provide comprehensive parameters. Therefore, the KUHP must adopt several materials from Perma 1/2020, with several modifications.